Heritages of Change Curatorial Activism and First-Year Writing - Tracy, Kisha G. (Open textbook library., 2024)
In first-year writing courses, it can often feel that we practice writing and research in a vacuum. Writing is about communication, and, if we do not feel that we have an audience, then it can seem like our writing has no purpose (even though practice of any kind will help us develop these skills). Heritages of Change: Curatorial Activism and First-Year Writing is a method for students to think about the social changes that were prevalent during the COVID years and remain important in their wake. Heritages of Change is a lens for thinking and writing about these ideas. Through curation and exhibition as an act of activism, students focus on a specific audience with whom they can communicate authentically about this dynamic world.